Local Non-Esterified Fatty Acids Correlate With Inflammation in Atheroma Plaques of Patients With Type 2 Diabetes - Mas, Sebastian; Martínez Pinna, Roxana; Martín Ventura, José Luis; Pérez, Raúl; Gómez Garre, Dulcenombre; Ortiz, Alberto; Fernández Cruz, Arturo; Vivanco, Fernando; Egido, Jesús (My University, 2010)
OBJECTIVE¿Atherosclerosis is prevalent in diabetic patients, but there is little information on the localization of nonesterified fatty acids (NEFAs) within the plaque and their relationship with inflammation. We sought to characterize the NEFA composition and location in human diabetic atheroma plaques by metabolo mic analysis and imaging and to address their relationship with inflammation activity. RESEARCH DESIGN AND METHODS¿Time-of-flight sec ondary ion mass spectrometry (TOF-SIMS) was used for metabo lomic analysis imaging of frozen carotid atheroma plaques. Carotid endarterectomy specimens were used for conventional immunohistochemistry, laser-capture microdissection quantita tive PCR, and in situ Southwestern hybridization. Biological actions of linoleic acid were studied in cultured vascular smooth muscle cells (VSMCs). RESULTS¿TOF-SIMS imaging evidenced a significant increase in the quantity of several NEFA in diabetic versus nondiabetic atheroma plaques. Higher levels of NEFA were also found in diabetic sera. The presence of LPL mRNA in NEFA-rich areas of the atheroma plaque, as well as the lack of correlation between serum and plaque NEFA, suggests a local origin for plaque NEFA. The pattern of distribution of plaque NEFA is similar to that of MCP-1, LPL, and activated NF- B. Diabetic endarterectomy specimens showed higher numbers of infiltrating macrophages and T-lymphocytes¿a finding that associated with higher NEFA levels. Finally, linoleic acid activates NF- B and upregulates NF- B¿mediated LPL and MCP-1 expression in cultured VSMC. DISCUSSION¿There is an increased presence of NEFA in diabetic plaque neointima. NEFA levels are higher in diabetic atheroma plaques than in nondiabetic subjects. We hypothesize that NEFA may be produced locally and contribute to local inflammation